Peran Edukasi dan Promosi Tenun Leny Bumpak sebagai Daya Tarik Budaya Provinsi Bengkulu - Febriansyah, Okta; Lestari, Nada Wafika; Zaki, Khozin; Indra, Yetti Afrida (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Leny Bumpak Weaving is one of the unique cultural heritages of Bengkulu Province which has historical, aesthetic, and economic value. Unfortunately, its popularity and use as a cultural attraction can still be considered low. This study aims to analyze the role of education and promotion of Leny Bumpak Weaving as a cultural attraction in Bengkulu Province. The methods used are participatory, educational, and collaborative approaches involving craftsmen, collaboration centers, the younger generation, and the wider community. The findings of this study indicate that Leny Bumpak Weaving has an important role in preserving local culture and developing cultural tourism in Bengkulu Province. Recommendations provided include improving digital-based promotional strategies and collaboration with tourism industry players. This study is expected to be a foundation for the development of Leny Bumpak Weaving as a cultural symbol and leading tourist attraction in Bengkulu.